PENGARUH DISIPLIN KERJA DAN PENGAWASAN TERHADAP KINERJA PEGAWAI DI RUMAH SAKIT UMUM DAERAH RUPIT KABUPATEN MUSI RAWAS UTARA - Wahyuni Damayanti; Maman Suparman (Jurnal Interprof, 2017)
This study aims to determine the effect of work discipline on employee performance, determine the effect on performance monitoring, as well as to determine the effect of labor discipline and monitoring the performance of employees at the General Hospital Musi Rawas Rupit North. This kind of research is a quantitative research, the population of this research is the Employee General Hospital area Rupit North Musi Rawas as many as 53 people, data collection technique used was t test and f. The test results with SPSS 20.0 for windows that do, show that there is influence between work discipline and monitoring to employee performance in the General Hospital Musi Rawas Rupit North, this can be known from the value of F obtained at 16.737 and sig. 0.00. This means that F count is greater then F table (3,183).